Community School - Integration School and Community: to mobilize is to transform? Experiences path of the year 2019 and adaptations in process during 2020 since the pandemic. (Revista Apotheke, 2021)
This article in art education aims to report the paths created, structured, groped and carried out by the project Community School - Integration School and Community in the neighborhood of Aclimação in the city of São Paulo in 2019 through the notions of cooperation (FREINET), free territories (RAGO) and experience (LARROSA). As a tool for interaction with the community during action research we use the concept of relational aesthetics (BOURRIAUD). From 2020 onwards with the coronavirus pandemic, there were changes in the project's action plan due to social isolation. Given this reality, we started a process of adaptations, experimenting again with other organizational, communicational, supportive and referral structures on virtual platforms together with the community. We use the idea of ​​a learning community (TORRES) where through our own strengths we seek to supply our needs. We reflect on our attempts to create and mobilize with different groups, neighbors and public officials in our territory and whether we can transform our local reality through praxis with the participation of various actors working in collaboration and partnership with public schools in the region.